2020
DOI: 10.1177/2151459320901997
|View full text |Cite
|
Sign up to set email alerts
|

Does Comanagement of Patients With Hip Fracture Influence 30-Day Outcomes

Abstract: Introduction: Comanagement of hip fractures is thought to optimize outcomes for these high-risk patients, but this practice is not universal. We aimed to determine whether comanagement of patients with hip fracture affects 30-day outcomes. Methods: The American College of Surgeons National Surgical Quality Improvement Program database was queried for all hip fractures between January 2015 and January 2017, totaling 15 461 patients (144 hospitals). Patients were divided into 3 cohorts: 11 233 comanaged througho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
(56 reference statements)
0
7
0
Order By: Relevance
“…Efforts have included initiatives to reduce the delay in time to surgical repair, defining the optimal type of repair (e.g., hemiarthroplasty vs total hip arthroplasty) and choice of anesthesia (regional vs general), and incorporating and evaluating surgical co-management between orthopaedic surgeons, geriatricians, and hospitalists. 30 - 33 There has been far less attention to addressing the gap in patient and caregiver understanding of HF prognosis. 10 , 11 While the internet provides many publicly available resources that discuss HF treatment and recovery, 34 , 35 these resources are not tailored to the prognosis or risk of the individual patient.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts have included initiatives to reduce the delay in time to surgical repair, defining the optimal type of repair (e.g., hemiarthroplasty vs total hip arthroplasty) and choice of anesthesia (regional vs general), and incorporating and evaluating surgical co-management between orthopaedic surgeons, geriatricians, and hospitalists. 30 - 33 There has been far less attention to addressing the gap in patient and caregiver understanding of HF prognosis. 10 , 11 While the internet provides many publicly available resources that discuss HF treatment and recovery, 34 , 35 these resources are not tailored to the prognosis or risk of the individual patient.…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 11 , 16 , 17 While interventions and increased knowledge on the risk factors contributing to 30-day mortality have improved outcomes, an understanding of the relative impact of specific risk factors on mortality remains unknown. 10 , 11 , 13 - 16 This study evaluated elderly patients undergoing hemiarthroplasty for femoral neck fractures to compare risk factors and generate a nomogram for understanding their mortality risk.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Despite attempts to reduce modifiable risk factors and improve medical co-management of patients, femoral neck fractures in elderly patients have high rates of in-hospital and 30-day morbidity and mortality with 1-year mortality rates approaching 35%. [10][11][12][13][14][15] Previous studies have shown decreased mortality and improved functional outcomes by reducing time to operating room for patients with femoral neck fractures. 12,13,[15][16][17] As patients with multiple medical comorbidities need preoperative optimization for efficient time to surgery; understanding risk factors may assist multidisciplinary teams in facilitating pre-operative management.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Similar trends and burden from hip fracture management are observed around the world, especially in developed nations. 3 Despite tremendous advances in geriatric fracture care with the advent of geriatric fracture centers and comanagement, [4][5][6][7] osteoporotic hip fractures are associated with high rates of morbidity and mortality to affected patients. [8][9][10][11] Reports of 1-year mortality rates are as high as 84.4% 8 for patients treated nonoperatively and 38% in operative patients.…”
Section: Introductionmentioning
confidence: 99%